Macam-Macam Strategi Kesuksesan Proyek Strategis: Studi Kasus Proyek “Yogyakarta International Airport” - Aziz, Mustofa Kamal; Wibowo, Kartono; Pratikso, Pratikso (VISA: Journal of Vision and Ideas, 2025)
The Yogyakarta International Airport Project was implemented for 730 days starting on July 16, 2018 to July 14, 2020. The New Airport in Kulonprogo Regency is targeted to gradually operate in April 2019. The purpose of this study is to identify the success factors and the sequence of variables that have the most influence on the implementation of Yogyakarta International Airport. In addition to the Project, it is to determine the relationship between variables in the successful completion of Yogyakarta International Airport. The form of research used is qualitative descriptive research conducted using a closed questionnaire method that is given directly to all stakeholders of the Yogyakarta International Airport Development Project. The results of this study show 6 factors that have the most influence with the order of variables from the most influential, namely, Labor, Goods and Services Procurement Strategy, Implementation Method, Equipment, Financing and Work Environment. While the negative relationship between variables in the Yogyakarta International Airport National Strategic Project is if Financing (X1) and Equipment (X2) increase, Success (Y) will decrease and vice versa.